Do pilot zones for green finance reform and innovation avoid ESG greenwashing? evidence from China - Tong, Youxia; Lau, Yeng Wai; Ngalim, Siti Manisah (Elsevier, 2024)
As ESG investments have grown, many companies are emphasizing them to impress capital markets and consumers with their responsibility and environmental consciousness. However, managers in unethical companies greenwashing ESG reports to keep clients. The present investigation employs quasi-natural experiment data obtained from a sample of 1200 Chinese A-share listed companies spanning the period from 2011 to 2021 to examine how the Green Finance Reform and Innovation Pilot Zone (GFRIPZ) affects ESG greenwashing. GFRIPZ can prevent publicly traded companies from ESG greenwashing. The statistical analysis of heterogeneity demonstrates that GFRIPZ in non-state-owned, mid-west, heavy-polluting, manufacturing industries reduces ESG greenwashing. GFRIPZ suppresses corporate ESG greenwashing better in companies with severe financial constraints and a poor corporate reputation. GFRIPZ's inhibition of corporate ESG greenwashing is enhanced by internal and external monitoring. This study shows how financial markets affect firms' ESG greenwashing. It helps implement GFRIPZ theoretically. It also recommends raising listed companies' awareness of ESG disclosure and reducing corporate ESG greenwashing.